Probability density estimation of public library users' visiting points using location information - Sugie, Noriko (American Society for Information Science and Technology. Meeting. Proceedings of the ... ASIST Annual Meeting, 2014)
ABSTRACT This study explores patterns of information‐seeking behavior of public library users through statistical analysis of quantitative data. A behavioral investigation using radio frequency identification (RFID) and a questionnaire survey were conducted at Chiyoda Public Library in Japan in 2012. Data was obtained on the time spent in the library, travel distance, traveling path, time spent browsing in each zone and time spent browsing books by subject. Probability density for visiting points in the library was estimated from users’ positional data gathered in the behavioral investigation in 2012. The results of the questionnaire survey were used to identify behavioral differences between two groups. As a result, it was found that users’ visiting points concentrated on the general book zone, users who borrowed materials walk around mainly in the general book zone, and users who did not borrow materials visited fewer points.